A serpente, espelho de Eva - Hilário Franco Júnior (Medievalista)
In the vast medieval iconography of the original Sin, the formula Adam and Eve on different sides of the Forbidden Tree, with the serpent facing the woman prevailed for a long time. In the thirteenth-fifteenth centuries an innovation would have great success: the serpent that induces Eve to sin has often been figured with feminine features. As for the historian there should be no unexplored facts, as irrelevant as they may seen at first glance, this article is an attempt to explain the purpose of those images. The hypothesis presented results from the articulation of three strong elements in the world view of that time: imagery language, analogical argumentation and misogynistic practice.